Alectinib in the treatment of ALK-positive metastatic non-small cell lung cancer: clinical trial evidence and experience with a focus on brain metastases. (February 2019) - Tomasini, Pascale; Egea, Julie; Souquet-Bressand, Maxime; Greillier, Laurent; Barlesi, Fabrice
Molecular profiling of metastatic nonsquamous non-small cell lung cancer (NSCLC) is required to guide the treatment strategy. Anaplastic lymphoma kinase ( ALK ) gene rearrangements are found in approximately 5% of lung adenocarcinomas and are associated with specific clinical features including a high risk of brain metastases. Crizotinib was the first ALK inhibitor developed and it demonstrated improved outcomes in patients with ALK -positive advanced NSCLC in comparison with chemotherapy. However, despite an initial response, all ALK -positive NSCLC patients develop acquired resistance to crizotinib. Because the most frequent mechanism of resistance is the development of a secondary ALK mutation, second (ceritinib, alectinib, brigatinib) and third-generation (lorlatinib) ALK inhibitors were developed. Alectinib is a second-generation ALK inhibitor and was shown to be effective for a broad spectrum of ALK rearrangements and ALK mutations. It was also shown to have high intracranial efficacy. In this article, we review clinical trial evidence of alectinib efficacy as well as publications reporting the experience of alectinib in daily practice, with a focus on brain metastases.